Relationship between Body Mass Index and Psychopathology: Analysis of Periodic Health Examination Results in 2021 - Rahmadiana Rahmadiana; Asnawi Abdullah; Marthoenis Marthoenis; Aripin Ahmad; Fahmi Ichwansyah (GLOBAL HEALTH SCIENCE GROUP, 2025)
Psychopathology is a mental disorder that can occur in police officers. Many factors influence psychopathology, one of which is obesity. This study was conducted to determine the relationship between body mass index and 10 psychopathology scales in police officers. Analytical research with a cross-sectional approach was conducted by analyzing secondary data from the Aceh Police Periodic Health Examination. A total of 709 police officers with records of physical examination results and mental health examinations using the Minnesota Multiphasic Personality Inventory (MMPI)-2 questionnaire participated in this study. Multivariate analysis used multiple logistic regression tests with a 95% confidence level. The results showed that respondents who were underweight or overweight were 52.33%. Statistically, body mass index was associated with depression (OR=2.57; 95%CI=1.22–5.40; p=0.012), psychopathic deviation (OR=1.43; 95%CI=1.03–1.99; p=0.030), paranoia (OR=1.72; 95%CI=1.05–2.81; p=0.029), psychasthenia/nerosa (OR=2.31; 95%CI=1.24–4.30; p=0.008) and schizophrenia (OR=2.13; 95%CI=1.32–3.43; p=0.002).